Sportwissenschaft - Schwartz B; 2; Baca A (Deutsche Zeitschrift für Sportmedizin, 2016)
Modern technologies like wearables and fitness apps are experiencing increasing popularity in assisting daily life activities. Based on the yearly socio-economic potential of up to 100 billion euros within the European Union, these technologiesarebecomingincreasingly interesting for scientists and physicians. In 2015there were more than 100.000 health-related apps. As a result of the continuously rising number, it is hard to stay up to date. Additionally, the enormous and steadily growing number of wearables in different fields of application (commercial, scientific, experimental) makes it impossible to keep an overview. Therefore, a critical review of current tendencies and developments has been performed. Depending on the target audience, the intricacy of such technologies reaches from simple step recognition for estimating physical activity in daily life to complex detection of disease-related events for medical diagnosis. Digital patient diaries, nutrition databases with more than two million integrated dishes as well as cardio-vascular monitoring devices are promising fields of application. Validity of the methods used and of the physical activity estimation has been shown by comparison to gold standard methods and clinical trials in many cases. Technical requirements, data security and missing implementation of behavior-changing elements can be seen as current risk factors of mobile health applications and therefore constitute the basis for better exploitation of the potential of these technologies.KEY WORDS: Wearables, Apps, Diagnostics, Health, Sport